Grouping patients with the same cancer or biological treatment on the same medicines administration day is an efficient tool. Issue 2 (12th March 2012) - De Juan, A.; Ibarra, E.; Peral, J.; Santos, A.; Ardanza, E.; Palacios, I.; Bustos, M.; Urrutia, A.; Torre, A. López de; Martínez-Bengoechea, M.J.
Abstract : Background: Minimisation of total drug expenditure within the healthcare system has become a rational goal in today's economic environment. In our setting, a 400-bed community hospital, antineoplastic and biological agents that require aseptic preparation account for 20% (3, 659, 400 €/year) of the total drug expenditure. When the shelf-life of the drug allows it, the Pharmacy stores partially-used vials in appropriate conditions until the next working day. But some drugs are not stable for more than 24 h when handled. Purpose: To assess the financial effect of grouping patients with similar treatments on the same day for medicines administration. Materials and methods: In order to reduce medicines wastage and to minimise expenditure The authors scheduled patients with similar treatments on the same day. The pharmacist selected those drugs with poor stabilities (less than 24 h) after the manufacturer's original presentation had been handled. He also evaluated the prescribing patterns and the nurses' workflow, the possibility of grouping patients with the same treatment and doing it in several days during the week, but trying not to overload any professional. The pharmacy department recorded the number of vials reused after each working day. Results: During the period January to August 2011, 340 vials of 12 drugs with poor stabilities (less than 24 h) were reused. This has led to a total saving of 3.6% (106, 311€) of the total costs of these drugs. Three drugs produced most of the cost savings: infliximab 52, 270 € (49% of the total, 76 patients, 309 doses), azacitidine 25, 036 € (24% of the total, 7 patients, 283 doses) and rituximab 11, 216 € (11% of the total, 51 patients, 170 doses). Conclusions: The relatively simple task of coordinating the day of drug administration of different patients can produce a very significant reduction in wastage and consequent financial gain.